Species and size composition of tuna longline catches in the Southes of Java, Indian ocean - Triharyuni, Setiya; Prisantoso, Budi Iskandar (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2012)
The growth of long line fleets operating in the south of Java resulted in smaller tuna caches both in number and size. Information on species and size composition of tunas is very important. This was done to obtain an overview of long line catch composition and its linear regression. The long liner’s catch data from south of Java in July, September, October 2005 and January 2006 are processed with a simple linear regression. The result shows that the yellow fin tuna is the dominant catch, where stingrays are the largest in by catch. From length-weight relationship analysis, which is divided into whole length-weight relationship and processed length- weight relationship, it is shown that the growth of big eye tuna is isometric, where albacore and yellow fin is negative allometric. Key words: Albacora, bigeye, Yelowfin, fish weight, fish length